Major Words in the History of Kings, Infantes and Navigators - Lemos Franca, Susani Silveira [UNESP] (Univ Federal Rio De Janeiro, 2018)
In Portugal in the 15th century, chronicles and travel accounts dedicated both to the past of the kingdoms and to the ever-deeper incursions into African lands are structured around certain general ideas, like ordering, not letting people forget, teaching those who are to come, and avoiding all and any falsehood. These two types of narratives with the role of organizing the past make use of a relatively homogeneous vocabulary that revolves around a few specific terms: grace, virtue and obedience. These words, as it will be examined in the present study, by their recurrence, reveal themselves as moralizing links or axes to justify and adorn the actions of the protagonists of the stories of that time: kings, infantes and navigators.
Keywords: 15th-century expansion; Portugal; chronicles; travel accounts; morality